2020
DOI: 10.1002/fsn3.1511
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chinese medicines on monacolin K production and related genes transcription of Monascus ruber in red mold rice fermentation

Abstract: Monacolin K (MK) is a secondary metabolite synthesized by polyketide synthases ofMonascus spp. In this study, the combined supplementation of three medicines, including Citri Reticulatae Pericarpium (CRP), Fructus crataegi (FC), and Radix Angelicae Dahuricae (RAD), were mixed with nonglutinous rice and were optimized by response surface methodology to enhance the production of MK in fermented red mold rice (RMR). Under the optimum condition, MK production achieved 3.60 mg/g, which was 41.18% higher than RMR wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…5 Monacolin K products are used as drugs to treat high blood lipids and high cholesterol; thus, increasing the production of monacolin K is important in studies on Monascus functional products. 6 Feedback inhibition of fermentation products is a key influence in many industrial processes, although there are relatively few studies on the feedback inhibition of monacolin K. Aspergillus terreus has been widely studied, and lovastatin in A. terreus is very similar to monacolin K in Monascus. Casas Lopez et al 7 found that the accumulation of lovastatin inhibits its synthesis through a feedback regulation mechanism in A. terreus.…”
Section: Introductionmentioning
confidence: 99%
“…5 Monacolin K products are used as drugs to treat high blood lipids and high cholesterol; thus, increasing the production of monacolin K is important in studies on Monascus functional products. 6 Feedback inhibition of fermentation products is a key influence in many industrial processes, although there are relatively few studies on the feedback inhibition of monacolin K. Aspergillus terreus has been widely studied, and lovastatin in A. terreus is very similar to monacolin K in Monascus. Casas Lopez et al 7 found that the accumulation of lovastatin inhibits its synthesis through a feedback regulation mechanism in A. terreus.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of a mix of three Chinese medicines to SSF cultures permitted an enhanced production of monakoline K by Monascus ruber [103]. These researchers also found six genes of M. ruber involved in monakoline K production.…”
Section: Adding External Precursors To Ssfmentioning
confidence: 86%
“…Ling et al screened 15 herbal medicines to investigate their effects on the production of lovastatin by Monascus M2-1 solid-state fermentation. The dosage and form of the added herbs significantly affected the fermentation results, and hawthorn juice, mulberry leaf powder, clove juice, and tangerine peel powder showed significant synergistic effects on the production of lovastatin by Monascus M2-1 fermentation [ 30 ]. Thus, Monascus can be widely used in herbal medicine for fermentation of pigment, lovastatin and or to improve the taste of herbal medicine, which improves the activity and medicinal value of traditional herbal medicine.…”
Section: Discussionmentioning
confidence: 99%